POOR CONCORDANCE BETWEEN NON-INVASIVE AND LOCALLY INVASIVE TECHNIQUES OF EVALUATION OF MICROVASCULAR MORPHOLOGY IN THE DETECTION OF HYPERTROPHIC REMODELING OF SMALL RESISTANCE ARTERIES. (June 2018) - De Ciuceis, C.; Caletti, S.; Coschignano, M.; Rossini, C.; Duse, S.; Docchio, F.; Pasinetti, S.; Semeraro, F.; Trapletti, V.; Nardin, M.; Rosei, C. Agabiti; Rizzoni, D.
Abstract : Objective: The evaluation of the morphological characteristics of small resistance arteries in human beings is not easy. The gold standard is generally considered to be the evaluation of the media to lumen ratio (MLR) of subcutaneous small vessels obtained by local biopsies and evaluated by wire or pressure micromyiography. However, non-invasive techniques for the evaluation of retinal arterioles were recently proposed, in particular two approaches seem to provide interesting information: scanning laser Doppler flowmetry (SLDF) and adaptive optics (AO); both of them provide an estimation of the wall to lumen ratio (WLR) of retinal arterioles, as well as of internal and external diameters and wall cross-sectional area. Design and method: In the present study we enrolled 12 normotensive subjects, 12 lean hypertensive patients (HP), 9 severely obese normotensive patients (ONP) and 8 severely obese hypertensive patients (OHP), undergoing an election surgical intervention. All patients underwent a biopsy of subcutaneous fat during surgery. Subcutaneous small resistance artery structure was assessed by wire micromyography and the MLR was calculated. WLR of retinal arterioles was obtained by Scanning Laser Doppler Flowmetry and AO (SLDF, Heidelberg Engineering, Heidelberg, Germany and RTX-1, Imagine Eyes, Orsay, France). In hypertensive/obese patients the characteristics of microvascular remodeling were assessed by the calculation of the remodeling and growth indices, according to Heagerty AM et al, Hypertension 1993; 21:391–391). The remodeling index quantifies the proportion of the increase in the MLR or WLR that may be explained by a re-arrangement of the same amount of wall material around a narrowed lumen (eutrophic remodeling), while the growth index quantifies the contribution of vascular smooth muscle cell hypertrophy or hyperplasia (hypertrophic remodeling).When eutrophic remodeling is present, the remodeling index is close to 100%. Results: are reported in the Table. Figure. No caption available. Conclusions: Our data suggest that the three methodological approaches seems are not completely concordant in the detection of hypertrophic remodeling, since data provided are in relative poor agreement. The presence of a relevant proportion of hypertrophic remodeling in obese patients (Hypertension 2011; 58:29–36), observed with micromyographic approaches, is not always confirmed by non-invasive approaches.